Revisión del perezoso terrestre Nothropus (Mammalia, Xenarthra, Tardigrada) del Pleistoceno de Argentina y Bolivia - Quiñones, Sofía Inés (2017)
The Nothrotheriinae Ameghino (Xenarthra, Pilosa) arerecorded in Argentina from the middle Miocene to the late Pleistocene. In the Quaternary of the current territories of Argentinaand Bolivia it is possible to recognize the existence of the genus Nothropus Burmeister, which includes three Pleistocene species,all of them known only by their type materials: (i) Nothropus priscus Burmeister (Santa Fe Province, Argentina); (ii) Nothropuscarcaranensis Bordas (Santa Fe Province, Argentina); (iii) Nothropus tarijensis (Burmeister) (Tarija Valley, Bolivia). This studyshows that N. priscus is a juvenile specimen and must be considered as a species inquirenda. In turn, the mandible morphologyof N. tarijensis is very different compared to that of N. priscus and N. carcaranesis. N. tarijensis shows a very robust dentary anda greater angle between the occlusal plane and the anterior margin of the ascending ramus, suggesting that this is a valid species.In summary, the evidence suggests that the diversity of Nothropus is limited to two species: N. carcaranensis in Argentina and N.tarijensis in Bolivia.